Analysis of Wind Potential as a Form of New and Renewable Energy at Manna in Bengkulu - Panggabean, Yehezkiel; Hermanto, Mochammad Fathurridho; Kencana, Elsa Rizkiya; Nandalianadhira, Nafisa (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
The energy from fossil fuels is declining due to modern society's high energy demands. This study investigates the potential of renewable energy, focusing on wind energy as a sustainable solution. It analyzes the Weibull and Rayleigh distributions to assess wind speed suitability in Bengkulu. The average wind speed at Manna Beach is 2.5 m/s, with a minimum of 0.01 m/s and a maximum of 10.01 m/s. Data validation tests were conducted at a height of 10 meters using Chi-Square and Kolmogorov-Smirnov methods. The chi-square test results indicated the values of 0.11 for Weibull and 0.42 for Rayleigh. The Kolmogorov-Smirnov test yielded value of 0.82 for Weibull and 0.84 for Rayleigh. Therefore, the suggesting Weibull was more suitable. Furthermore, using the Aventa AV-7 wind turbine, an annual output of 11,096.29 kWh can supply 30% of the electricity demand, which requiring 199 turbines. Ultimately, 40 turbines effectively contribute 6% or 440,621.94 kWh of total demand.